OBLIGATIONS OF LAND RIGHTS HOLDERS TO MANAGE THEIR OWN AGRICULTURAL LAND - Suhartono Suhartono; Rahmatul Hidayati; Ahmad Siboy (SOSIOEDUKASI, 2026)
Agricultural land is a strategic asset in national development because it plays a direct role in maintaining food security and community welfare. However, the process of urbanization, industrialization, and weak legal supervision has led to massive land conversion and an increase in absentee land ownership practices (guntai). Landowners who do not manage their land directly cause a lot of land to become unproductive, illegally transferred, or used as an object of price speculation. This condition causes inequality in land distribution and hinders the goal of agrarian reform as mandated by the UUPA. Therefore, this study examines in depth the "Obligations of Land Rights Holders to Manage Their Own Agricultural Land", focusing on how the normative regulation of these obligations and the legal consequences for rights holders who do not implement them. This study formulates two main research questions: how the obligation of land rights holders to cultivate their own agricultural land is regulated in Indonesian legislation, and what the legal consequences are for those who fail to fulfill this obligation. The research employs a normative juridical method with statutory and conceptual approaches. The legal materials used include primary sources such as the 1945 Constitution, the Basic Agrarian Law, Government Regulation No. 224 of 1961, Law No. 41 of 2009, Government Regulation No. 20 of 2021, and other related regulations, as well as secondary sources consisting of literature and academic journals, and tertiary legal materials. The results of the study show that the obligation of the right holder to manage agricultural land itself is a manifestation of the principle of the social function of land as stipulated in Article 6 of the UUPA. The provisions regarding the prohibition of absentee land ownership are affirmed in Government Regulation No. 224 of 1961, which requires agricultural land to be managed directly by its owners in order to prevent land concentration, speculative practices, and the occurrence of abandoned land. This obligation is also strengthened through the policy of protecting sustainable food agricultural land. Right holders who do not manage their land can be subject to various legal consequences, such as: control and takeover as abandoned land, reduction or revocation of land rights, and redistribution to other parties through the land reform program. Thus, the obligation to manage agricultural land itself is not only an administrative norm, but an important instrument to achieve agrarian justice and ensure the sustainability of national food security.